2021
DOI: 10.3346/jkms.2021.36.e321
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on the Mental Health of Adolescent Students in Daegu, Korea

Abstract: Background In February 2020, as coronavirus disease 2019 (COVID-19) spread rapidly in Daegu, South Korea, students in that region experienced many emotional difficulties. In this study, we analyzed the stress and emotional crisis experienced by students during the COVID-19 pandemic, its causative factors, and the factors that affect negative emotions. Methods We identified the demographic information related to the experiences of unbearable stress and emotional crisis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…In this study, 13.5% of students reported being always in a negative mood during online classes, which is consistent with other studies on adverse mental health among Asian adolescents that reported percentages between 7.1% and 17% [ 21 , 22 , 23 ]. Adolescence, the transition between childhood and adulthood, was vulnerable to mental-health issues during the pandemic disruption due to maturity and physical, emotional, personality, and social development changes.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, 13.5% of students reported being always in a negative mood during online classes, which is consistent with other studies on adverse mental health among Asian adolescents that reported percentages between 7.1% and 17% [ 21 , 22 , 23 ]. Adolescence, the transition between childhood and adulthood, was vulnerable to mental-health issues during the pandemic disruption due to maturity and physical, emotional, personality, and social development changes.…”
Section: Discussionsupporting
confidence: 92%
“…In a study conducted in Daegu Metropolitan City in South Korea, where the number of confirmed cases was high early in the pandemic, the prevalence rates of anxiety and depression in adolescents were 12.3% and 19.8%, respectively, which are higher than those in the present study. 22 In addition, studies conducted at the height of the epidemic in China reported depression prevalence estimates ranging from 19% to 46%. A national survey reported that 25.5% of South Korean adolescents were depressed, as based on a single question: “Has your life been disrupted by depression for 2 weeks or more in the past 12 months?” In contrast, the present study used a dedicated depression scale to measure the prevalence of moderate-to-severe depression; the use of this more specific measure of depression may account for the difference between the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with many local South Korean studies. Jimhee's survey showed that the prevalence of depression among the general population of Korea at the beginning of the pandemic was 19%( 43 ), Lee's study on adolescents in Daegu, South Korea, during the COVID-19 pandemic showed that 19.8% and 12.3% of students experienced depression and anxiety, respectively ( 44 ), Hoo's study of adults aged 20 to 49 in Chungnam Province, South Korea, during the COVID-19 pandemic found that 18.8% of participants had symptoms of depression ( 45 ). In Kim's study of 180 nurses during the pandemic, 30.6% had moderate or higher levels of depression ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depression rates were fairly high for both student groups, since the Chinese international students in South Korea have a (45). In Kim's study of 180 nurses during the pandemic, 30.6% had moderate or higher levels of depression (46).…”
Section: Differences In Depression Between Chinese International Stud...mentioning
confidence: 96%